Exploring Challenges in EFL Learning and Acquisition: A Case Study of a Rural High School in Central Java, Indonesia - Kristanto, Feri; Umami, Mashlihatul; Zulfah, Siti; Fatin, Manar Abdurra'uf (Journal of Language and Literature Studies, 2025)
This qualitative descriptive study investigates the challenges faced by students in learning and acquiring English as a foreign language (EFL) at MA Muallimin Rowoseneng, a rural private high school in Central Java, Indonesia. Using semi-structured interviews and thematic analysis, data were collected from 15 students and one teacher to explore barriers across four language domains: speaking, listening, reading, and writing, as well as broader acquisition difficulties. Findings reveal that students grapple with internal factors such as low motivation, lack of self-confidence, and mother tongue interference, compounded by external challenges like an unsupportive linguistic environment and inadequate learning facilities. Thematic analysis highlighted recurring issues in pronunciation, vocabulary, and grammar, alongside systemic gaps in exposure and practice opportunities. The study underscores the interplay between psychological, environmental, and pedagogical barriers, emphasizing the urgent need for targeted interventions to enhance rural EFL education. Recommendations include fostering motivational strategies, integrating contextualized teaching methods, and improving infrastructural support to create immersive English-learning environments. This research contributes to understanding EFL challenges in resource-constrained rural settings and informs stakeholders on actionable steps to bridge educational disparities.